Development of Agrotourism Potentiality in Kampung Kopi Amadanom, Malang - Edriana Pangestuti; Latifah Hanum; Lestari Eko Wahyudi (Journal of Indonesian Tourism and Development Studies, 2018)
Agro tourism is the community-based tourism activities that utilize the agricultural business as a tourist attraction that has many positive impacts which can improve the economy of society, especially in the form of society’s income, open employment opportunities and business opportunities (entrepreneurship). This research aim was to develop the concept of agro tourism in the largest coffee producing area in Malang Regency that is in Amstirdam (Ampelgading, Sumbermanjing Wetan, Tirtoyudo, and Dampit). This study used a qualitative approach by observing the four areas to see the potential of each region. SWOT technique was used to analyze data and the results showed that Dampit is one area that has more potential attractions than other regions. One area in Dampit that has the potential to be developed into agro tourism is Kampung Kopi Amadanom. The results of this research indicated that the effort for developing Kampung Kopi Amadanom was still not maximal due to the lack of local government support and also lack of quality supporting resources. This research suggested by using development model and applying appropriate strategy, it could provide and increase benefits not only for Kampung Kopi Amadanom but also for Malang generally.Keywords: Agro-tourism, Amadanom, Coffee Agro-tourism, Tourism.